Fostering independence, participation, and healthy aging through technology : workshop summary - Lustig, Tracy A.; Olson, Steve, 1956- (Online access: National Academy of Sciences National Academies Press., 2013)
"In 2012 the IOM and NRC joined together to establish the Forum on Aging, Disability, and Independence to provide a neutral venue for broad-ranging discussions among the many stakeholders involved with aging and disability. The goals of the forum are to highlight areas in which the coordination of the aging and disability networks is strong, examine the challenges involved in aligning the aging and disability networks, explore new approaches for resolving problem areas, elevate the visibility and broaden the perspectives of stakeholders, and set the stage for future policy actions. Forum sponsors and members include federal agencies, health professional associations, private sector businesses, academics, and consumers. Fostering Independence, Participation, and Healthy Aging Through Technology summarizes this workshop"--Publisher's description.